STEVE - Spatial-Temporal View Editor for Authoring Hypermedia Documents - Mattos, Douglas Paulo de; Muchaluat-Saade, Débora Christina Muchaluat (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Interactive multimedia applications are available in many platforms such as smartphones, computers and digital TVs. In addition, the production of multimedia content has been growing increasingly and facilitated due to easier access to these devices. In this scenario, the creation of multimedia applications has gained importance. There are several commercial tools that allow building multimedia presentations using the timeline paradigm for users with no programming knowledge. However, these tools inherit the timeline authoring paradigm limitations. In order to facilitate hypermedia document authoring for users with no knowledge of programming and avoid the timeline paradigm limitations, this paper proposes an event-based hypermedia document model and a graphical editor, which is based on this model, for spatiotemporal view editing of a document. The proposed tool is called STEVE, Spatio-Temporal View Editor, which supports the definition of viewer interactions. Besides, STEVE exports hypermedia applications to NCL and HTML5 documents to accomplish different execution platforms.